Into the bright unknown - Carson, Rae (Carson, Rae. Gold seer trilogy, 2018)
During the 1850s Gold Rush in California, Leah Westfall has encountered danger, hidden magic, and the harsh reality of loss, but she has also found true friends, love, and a place to call home. However, Lee's magic makes her and her friends the target of a billionaire who threatens all Lee holds dear. Lee and her loved ones are determined to fight back and save themselves and their livelihood.